Madrasah Ibtidaiyah Dari Masa Ke Masa: (Kajian Historis Tentang Madrasah Ibtidaiyah) - Syaifur Rohman (LP3M Universitas Islam Zainul Hasan Genggong, 2016)
Embryos derived from religious education schools, which then evolved into the madrassa. Pesantren is the oldest religious educational institutions in Indonesia and is still showing its existence as one of the places to print the future generations who qualified in the field of religion. Do not want to fall behind in the field of further education schools and founded the madrassa as a container to complement the existing shortage of cargo lessons dipesantren. Madrasah can be a bridge between schools and formal schools are both located on two different poles. As the formal educational institutions madrasah carrying high ideals to prepare a generation that is not only intellectually clever but also capable of being the generation that ‘alim other words madrassa want to print a generation of intellectuals who’ alim. But unfortunately the trip madrasah into formal education institutions that ideal is not as smooth hopes and ideals of the beginning of the founding father. Problems began to emerge from the curriculum, lack of management until the status of madrassas in the Act. Besides the development paradigm that the madrasas are second-class schools triggered the public interest against the lack of education in madrasas. Starting in 1946 until now madrasas have undergone various phases in the Act. But the real contribution madrasas began to be recognized society, so that they begin to look madrasah as a place of education for their children. As proof that more and more madrasas that have quality similar or even better than formal schooling in general.